Can aerosols-generating dental, oral and maxillofacial, and orthopedic surgical procedures lead to disease transmission? An implication on the current COVID-19 pandemic - Al-Moraissi, Essam Ahmed; Kaur, Amanjot; Günther, Frank; Neff, Andreas; Christidis, Nikolaos (Frontiers in Oral Health, 2022)
Various dental, maxillofacial, and orthopedic surgical procedures (DMOSP) have been known to produce bioaerosols, that can lead to the transmission of various infectious diseases. Hence, a systematic review (SR) aimed at generating evidence of aerosols generating DMOSP that can result in the transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), further investigating their infectivity and assessing the role of enhanced personal protective equipment (PPE) an essential to preventing the spreading of SARS-CoV-2 during aerosol-generating procedures (AGPs). This SR was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement (PRISMA) guidelines based on a well-designed Population, Intervention, Comparison, Outcomes and Study (PICOS) framework, and various databases were searched to retrieve the studies which assessed potential aerosolization during DMOSP. This SR included 80 studies (59 dental and 21 orthopedic) with 7 SR, 47 humans, 5 cadaveric, 16 experimental, and 5 animal studies that confirmed the generation of small-sized < 5 μm particles in DMOSP. One study confirmed that HIV could be transmitted by aerosolized blood generated by an electric saw and bur. There is sufficient evidence that DMOSP generates an ample amount of bioaerosols, but the infectivity of these bioaerosols to transmit diseases like SARS-CoV-2 generates very weak evidence but still, this should be considered. Confirmation through isolation and culture of viable virus in the clinical environment should be pursued. An evidence provided by the current review was gathered by extrapolation from available experimental and empirical evidence not based on SARS-CoV-2. The results of the present review, therefore, should be interpreted with great caution.